2005
DOI: 10.1080/14681990500186266
|View full text |Cite
|
Sign up to set email alerts
|

Improving child and family outcomes following complicated births requiring admission to neonatal intensive care units

Abstract: This paper reviews current research regarding the impact of birth complications, such as preterm labour, on parents and the nuclear family system. Specifically, how parents cope with the neonatal intensive care unit (NICU) experience and the associated decision-making tasks required during complicated births will be investigated. Consequences of poor adaptation to prematurity for the parent, family and infant relationships will also be discussed. The importance of informed decisionmaking, perceived control, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Conner and Nelson (1999) found that parents need caring, communication, consistent information, education, follow up, adequate pain management, participation in the infant's care, and proximity to and support with their fragile infant. Phillips and Tooley (2005) documented that mothers who did not see or touch or have proximity to their babies often felt distressed. According to Hall (2005aHall ( , 2005b, because the process of parenting is a protecting and loving phenomenon, parents should participate in the care of their sick, fragile infant in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…Conner and Nelson (1999) found that parents need caring, communication, consistent information, education, follow up, adequate pain management, participation in the infant's care, and proximity to and support with their fragile infant. Phillips and Tooley (2005) documented that mothers who did not see or touch or have proximity to their babies often felt distressed. According to Hall (2005aHall ( , 2005b, because the process of parenting is a protecting and loving phenomenon, parents should participate in the care of their sick, fragile infant in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…The contents of the booklet, About my premature baby: Things a father must know, was developed by the authors in consultation with neonatal nursing experts and fathers of premature infants (See supporting information Data S1 in the online version of the article in Wiley Online Library). It was based on House's four types of support and findings from previous studies (Perlman , Fowlie & McHaffie , Schaffer & Yucha , Goodman , Hynan , Phillips & Tooley , Arockiasamy et al . , Halm , Lee et al .…”
Section: The Studymentioning
confidence: 99%
“…The contents of the booklet, About my premature baby: Things a father must know, was developed by the authors in consultation with neonatal nursing experts and fathers of premature infants (See supporting information Data S1 in the online version of the article in Wiley Online Library). It was based on House's four types of support and findings from previous studies (Perlman 2003, Fowlie & McHaffie 2004, Schaffer & Yucha 2004, Goodman 2005, Hynan 2005, Phillips & Tooley 2005, Arockiasamy et al 2008, Halm 2009, Lee et al 2009a, 2009b. Topics in the booklet included 'the equipment the baby used', 'baby's developmental care in the NICU', 'baby's nutrition', 'baby's appearance', 'what your baby is doing', 'what you can do with your preterm baby when you are at the NICU', and 'relaxation tips for the fathers'.…”
Section: Interventionsmentioning
confidence: 99%
“…2007), all of which are inherent in breastfeeding. The mother's unique involvement in the feeding and care of her infant may also alleviate her shock, fear and grief following the birth, and reduce the estrangement from her baby associated with care in a neonatal unit (Phillips & Tooley 2005; Redshaw & Hamilton 2006; Flacking et al . 2007; BLISS 2008).…”
Section: Introductionmentioning
confidence: 99%